Long term COST-minimization analysis of robot-assisted hysterectomy versus conventional laparoscopic hysterectomy. - Martínez-Maestre, María A.; Melero-Cortés, Lidia María; Coronado, Pluvio J.; González-Cejudo, Carmen; García-Agua-Soler, Nuria; García-Ruiz, Antonio J.; Jódar-Sánchez, Francisco (BMC, 2019)
Background: The aim of this study is to carry out the economic evaluation, in term of a cost-minimization analysis that considers healthcare costs and indirect costs, of robot-assisted hysterectomy (RAH) compared with conventional laparoscopic hysterectomy (CLH) in female adults scheduled for total laparoscopic hysterectomy for benign conditions. Methods: Cost-minimization analysis based on an analytic observational study of prospective cohorts with a fiveyear time horizon. Eligible participants were all female adults scheduled for total laparoscopic hysterectomy for benign conditions at tertiary hospital. The economic evaluation was conducted from a Spanish National Health Service and societal perspective, including healthcare costs and indirect costs. The costs are expressed in Euros from the year 2015. Results: One hundred sixty nine patients were analyzed, 68 in the RAH group and 101 in the CLH group. Average cost for the RAH group was €8982.42 compared to €8015.14 for the CLH group (incremental cost €967.27; p = 0.054). Healthcare cost is the most important component of total cost and represents 86.4% for the RAH group and 82.3% for the CLH group. The difference of €1169 (p = 0.01) in the average healthcare cost is mainly due to the cost of purchasing and maintaining the equipment (difference of €1206.39 in favor of RAH; p < 0.005). With regard to indirect costs, for patients in the RAH group the costs associated with loss of productivity were lower (difference of €203.42; p = 0.17), while the cost of trips to the hospital was higher (difference of €1.98; p = 0.66) in respect to CLH. Conclusions: Our findings reveal similar effectiveness between RAH and CLH, although CLH is the more efficient option from the point of view of an economic analysis based on cost-minimization.
Keywords: Útero - Técnicas quirúrgicas; Laparoscopia; Economic evaluation; Laparoscopy; Hysterectomy; Robotic surgery